(3GdEWGQ GdYGe hCKQgG aj GdShb GdeGdj heJZjQGJ GdEbJUGO Gdcdjs - (3fRGQ cGXe(B, (3GdNjcGfjs; (3MjOQ jhfS GdehShj(B, s ((3YeGf(B:s (3OGQGdjGRhQj GdYdejI ddfTQ hGdJhRjY(B,s, 2015)
(3jVe GdSjGSI GdfbOjI aj efXhQ GdfXQjGJ GdGbJUGOjI, GdSjGSI GdeGdjI YHQ GdfXQjGJ GdGbJUGOjI, aGYdjI GdSjGSJjf GdfbOjI hGdeGdjI hEecGfjI GdJfSjb HjfgeG, CKQ GdSjGSGJ GdGbJUGOjI aj GdShb GdeGdj, GdeJZjQGJ GdfbOjI hGdeGdjI hCKQgG Ydi HYV eJZjQGJ GdEbJUGO Gdcdj aj eUQs
(3bGFeI GdeQGLY U(B.331 (3GdedGMb U(B.345s
Keywords: (3GdEbJUGO Gdcdjs; (3GdJNWjW GdEbJUGOjs; (3GdSjGSI GdEbJUGOjIs; (3GdSjGSI GdeGdjIs; (3GdSjGSI GdfbOjIs